Role of Microfinance in Economic Empowerment of Women in Lahore, Pakistan: A Study of Akhuwat Supported Women Clients - Shaheen, Imrab; Hussain, Iftikhar; Mujtaba, Ghulam (International Journal of Economics and Financial Issues, 2018)
Economic empowerment include, women decision making at different levels; women participation in economic and social matters, women’s access and control over resources, access to options, access to have health and education facilities, control and choice to use resources, options to make life choices. Microfinance has been seen instrumental in economic empowerment of women. The study focused on the impact assessment of microfinance on economic empowerment of women in Lahore, Pakistan. A disproportionate stratified random sampling technique was used to draw a sample of 175 respondents/female clients of Akhuwat foundation from Lahore city. Data were collected through questionnaire containing five point Likert scale. Some exemplary cases have also been added in order to observe and understand the phenomenal success of poor women. Data were analyzed through Linear regression performed on SPSS.v.20. It has been found that microfinance has a considerable impact on economic empowerment of women. The research reveals that women empowerment is linked with social intermediation/guidance and enterprises development which seems to have a lasting impact in achieving financial independence. Findings also confirm that micro-finance may serve as a catalyst towards economic empowerment. Keywords: Microfinance, Economic Empowerment, Social intermediation, Akhuwat Foundation JEL Classification: G21